Magnetic resonance-based thermometry during laser ablation on ex-vivo swine pancreas and liver. Issue 7 (July 2015) - Allegretti, G.; Saccomandi, P.; Giurazza, F.; Caponero, M.A.; Frauenfelder, G.; Di Matteo, F.M.; Beomonte Zobel, B.; Silvestri, S.; Schena, E.
Highlights We provided first data of magnetic resonance (MR) thermometry on pancreas. We tested the effectiveness of two T1-wighted sequences for MR-based thermometry on liver, and afterward on pancreas. Fiber Bragg Grating sensors (FBGs) were employed for reference temperature monitoring. We investigated laser ablation (LA) on pancreas as possible novelty in clinical practice.